A utility-tailored methodology for integrated asset management of urban water infrastructure - Alegre, H. (2012)
This paper presents the integrated methodology for infrastructure asset management (IAM) developed in AWARE-P, an R&D project aimed at producing adequate and effective support tools for assisting urban water utilities in decision making and rehabilitation planning (www.aware-p.org). The proposed methodology addresses all three planning and decisional levels (strategic, tactical and operational) and follows a PDCA-inspired cycle. The methodology assesses the water systems and any planning solutions along the cost, risk and performance dimensions, with a variety of standardised assessment methods and models proposed for each. It differs from existing approaches in the incorporation, into a single organised framework, of the entire IAM process with an integrated, long-term vision of the urban water network – looking at the infrastructure as a system, and not as a mere sum of individual assets. The paper describes the approach and illustrates its application with reference to the several business cases already undertaken.